Investigation Of Aerodynamic Characteristics Of A Wing Model With Rgv Winglet - Gopal Krishnan, Sivaraj (2017)
This work describes the aerodynamic characteristics of an aircraft model wing with RGV winglet. A Computational Fluid Dynamics (CFD) study using ANSYS 15.0 is conducted to study the effect of the RGV winglet on a rectangular wing. The wing consists of 660 mm span and 121 mm chord length where the aspect ratio is 5.45. The NACA 65(3)